2010
DOI: 10.1177/097491010900200105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Global Financial Crisis on Emerging and Frontier Markets in Africa

Abstract: The financial crisis that has swept through the global economy since the middle of 2007 has led to a sharp deceleration in economic growth in the emerging and frontier market economies in Africa. The record growth performance of gross domestic product of about 6 percent per annum that Africa had experienced during 2002–07 has been seriously interrupted. The consequences on employment and poverty of this interruption could be dire. In the end, the economic impact of the crisis on Africa will depend crucially on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…26. This has created significant stress in these countries since they ran up dangerously large current account deficits (except for Russia) and took on substantial international debt (Boorman, 2009). In other words, as our study demonstrated, the countries with large current account deficits were disproportionately hit by the crisis as foreign investors deleveraged and capital flows dried up.…”
Section: Discussionmentioning
confidence: 71%
“…26. This has created significant stress in these countries since they ran up dangerously large current account deficits (except for Russia) and took on substantial international debt (Boorman, 2009). In other words, as our study demonstrated, the countries with large current account deficits were disproportionately hit by the crisis as foreign investors deleveraged and capital flows dried up.…”
Section: Discussionmentioning
confidence: 71%
“…Reinhart and Rogoff (2008b) observed that the antecedents and aftermath of banking crises in advanced and emerging markets have a common pattern. Similarly, many recent studies (Arner & Schou-Zibell, 2011; Boorman & Christensen, 2010; Fidrmuc & Korhonen, 2010) noted that the crisis had a similar effect in advanced economies and developing economies. Subsequently, Reinhart and Rogoff (2009) found that the asset market collapsed and protracted, then real housing prices tumbled by an average 35 per cent over six years, while equity prices plummeted sharply, an average downturn of 55 per cent over about three and half years.…”
Section: Introductionmentioning
confidence: 70%